The Ranking of Starbucks in The Eyes Of The Public And Its Competitiveness in The Industry - Sin, Liem Gai; Ibrahim, Haslindar; Abdul Rahim, Noor Fareen; Baliyan, Meenu; Mohd Fauzi, Farah Irdina Binti; Shamsuddin, Fatin Natasya Binti; Fa, Xin Yi; Shan, Gan Li; Rastogi, Shourya; Tayal, Nupur; Sangal, Shivansh; Chaudhary, Vikrant; Kee, Daisy Mui Hung (AIBPM Publisher, 2024)
Starbucks Corporation is a coffee brand with a very long history. It is the world's largest coffeehouse chain. With the development of the age, people have shown a lot of demand for drinks that can help refresh and have shown their great demand for refreshing drinks in their busy daily lives. This research examines how the general public views Starbucks and its competitive position within the coffeehouse sector focusing on location, environment, food & beverage, and service quality variables. For research purposes, an online survey was distributed to a designated number of people in Malaysia and India for data collection. The data was analyzed using the Statistical Package for the Social Sciences (SPSS). The study shows that Starbucks has effectively built a robust brand and garnered considerable public awareness, solidifying its position as a key player in the industry. Starbucks has attained a prominent standing in the public's view owing to its strong brand recognition and positive perception, influenced by factors like strategic locations, inviting ambiance, premium food and beverage offerings, and outstanding service quality. Among all these factors, the location of the Starbucks store is the primary factor affecting the public's love for Starbucks. Recognizing the importance of these factors could offer valuable insights for businesses aiming to enhance their standing and competitiveness